A HEALTHY LIFESTYLE IS THE BASIS OF HEALTH (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, the role of healthy lifestyle in society is incomparable. There are priority tasks such as forming a healthy way of life, raising a highly moral and well-rounded person who has an independent mind and lives with a purpose.